2018
DOI: 10.2474/trol.13.157
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Tribofilm Growth and Tribological Properties of Tribofilms Formed from Zinc Dialkyl Dithiophosphate (ZDDP) and Molybdenum Dialkyl Dithiocarbamate (MoDTC)

Abstract: Tribofilms are critical for the management of wear and the control of friction. This study focused on the tribological properties of tribofilms to clarify their antiwear and low-friction mechanisms. By monitoring tribofilm growth and measuring friction-coefficient mapping, we found that a tribofilm was generated in a dynamic process of formation and wear. The friction coefficient decreased with an increase in film thickness. The friction coefficient distributions of the tribofilms depended on the chemical natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Shi et al found that similar low friction mechanism was observed on the graphene/copper/hydroxypropyl-methylcellulose coating [26]. Additives in oil lubricants, which are also widely used in industry, generate additive-derived tribofilms on sliding surfaces due to sliding heat and high shear stress at the real contact area, resulting in high wear resistance and low friction [27][28][29][30][31][32][33][34][35]. Both systems can be reconsidered as excellent systems designed to transition to the desired state (e.g., low friction surfaces) upon the occurrence of the phenomenon to be controlled (e.g., friction).…”
Section: Introductionmentioning
confidence: 76%
“…Shi et al found that similar low friction mechanism was observed on the graphene/copper/hydroxypropyl-methylcellulose coating [26]. Additives in oil lubricants, which are also widely used in industry, generate additive-derived tribofilms on sliding surfaces due to sliding heat and high shear stress at the real contact area, resulting in high wear resistance and low friction [27][28][29][30][31][32][33][34][35]. Both systems can be reconsidered as excellent systems designed to transition to the desired state (e.g., low friction surfaces) upon the occurrence of the phenomenon to be controlled (e.g., friction).…”
Section: Introductionmentioning
confidence: 76%
“…This highlighted the enhanced antiwear property of ZDDP when combined with MoDTC, as opposed to the increased wear observed in ZDDP alone scenario. 108 Consequently, the inclusion of MoDTC with ZDDP yields an improved antiwear performance for soft surfaces. In a similar study involving ADC12 alloy, blending of tert-butoxy-functionalized h-BN nanosheets (h-BN-TBO) with ZDDP, the introduction of the latter into the ZDDP-containing lubricant led to a remarkable improvement in the tribological properties owing to the synergistic interaction between the blend constituents.…”
Section: ■ Influence Of Supplementary Additives On Tribofilm Formatio...mentioning
confidence: 99%
“…The blending of MoDTC with ZDDP has been observed to retard ZDDP tribofilm growth owing to the competitive adsorption phenomena between ZDDP and MoDTC . In a macroscale investigation, Lu et al reported a synergistic effect when an optimal concentration of MoDTC was mixed with ZDDP, leading to the transformation of ZDDP into an antiwear zinc phosphate glass tribofilm, while MoDTC decomposed to a MoS 2 tribolayer, inducing a low coefficient of friction on the surface. The adsorption of these low-friction MoS 2 layers in the wear scar is promoted by the generation of FeS 2 , N-containing species and phosphate layers, which collectively serve as protective layers for retaining the MoS 2 . The inclusion of MoDTC in ZDDP-containing lubricant resulted in only a marginal increase in wear compared to ZDDP alone, and this wear was still lower than that observed with the base oil .…”
Section: Influence Of Supplementary Additives On Tribofilm Formation ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that MoDTC can activate reciprocating tests. Lu [28] monitored the process of friction films formation between MoDTC and ZDDP, and proved that MoDTC accelerated the formation of ZDDP friction films. Xu [29] used Raman microscope and atomic force microscope to study the relationship between the formation and removal of MoDTC/ZDDP friction films.…”
Section: Introductionmentioning
confidence: 98%